STUDI LITERATUR: IMPLEMENTASI GURU SEBAGAI FASILITATOR DALAM PROSES PEMBELAJARAN BIOLOGI ABAD-21 DI SEKOLAH MENENGAH ATAS - Nuria Imamah Thurrodliyah; Kukuh Munandar (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
The development of the times expects a paradigm shift in the teacher's teaching pattern, which was originally a source of information for students and always dominated activities in the classroom, changing towards a paradigm that positions the teacher as a facilitator in the learning process and there is always interaction between teachers and students and students and students in class. The approach in this study uses a type of research in the form of a literature study or literature study. This research method is a qualitative research by collecting references consisting of several previous studies compiled to draw conclusions. Most of our educators position themselves as facilitators in the learning process carried out. This requires the development and improvement of the concept of providing facilities to students such as the differentiated learning approach.